Estimativa dos coeficientes de cultura do milho e sorgo a partir da área foliar e altura do dossel: avaliação utilizando um modelo de balanço hídrico - Gonçalves, Andressa Fuzer (2025)
In a scenario involving global climate change, water scarcity and population growth, it is crucial to manage the water used by crops optimally. One way of achieving this is to estimate crop evapotranspiration (ETc), which is normally ccomputed using weather variables and the physical, physiological and aerodynamic parameters that govern the evapotranspiration process. In this approach, ETc is obtained by multiplying the reference evapotranspiration (ETo) by a crop coefficient (Kc). While the Kc−ETo approach is straightforward to use, its application requires a high degree of precision in calculation and measurement, particularly when obtaining crop coefficients for a specific crop from surface measurements. Another approach considered in the FAO56 bulletin is the dual crop coefficient method, which consists of the sum of a dual crop coefficient (Kcb) and an evaporation coefficient (Ke). This results in Kc, where Kcb represents crop transpiration (Tc) and Ke represents soil evaporation (Es). Recently, new approaches to estimating Kc and Kcb (the A&P method, proposed by Allen and Pereira, 2009) have been developed based on the canopy fraction covering the ground (fc), leaf area index (LAI) and canopy height. Thus, this study aimed to estimate the simple (Kc) and basal (Kcb) crop coefficients of corn and sorghum plants grown on different soil textures, based on the leaf area index (LAI) and plant height. The data used were obtained from studies conducted in drainage lysimeters in a rainout shelter. The actual ETc and its components (actual crop transpiration and soil evaporation) were estimated using the SIMDualKc model in order to evaluate the quality of the A&P methodology (Kcb A&P). The results demonstrate the SIMDualKc model’s excellent performance in estimating available soil water dynamics, with b0 values ranging from 1.00 to 1.02 and RMSE < 5.31 mm for corn and b0 values ranging from 0.98 to 1.03 and RMSE <5.25 mm for sorghum. The relationship between accumulated degree days (GDD) and the development of corn and sorghum plants produced good statistical outcomes, with b0 close to 1.0, RMSE<0.30, and R2≥0.96, resulting in a normalized RMSE of less than 10% for irrigated corn and sorghum subjected to terminal soil water deficit (TSWD). The calibration of Kcb A&P using SIMDualKc demonstrated that biophysical characteristics can be used to estimate the water use of corn and sorghum, with R2 greater than 0.95 and a b0 between 0.99 and 1.06. When the two approaches are compared, the results demonstrate the suitability and ease-to-use of the A&P approach for supporting irrigation scheduling and improving water management in irrigated crops.